Forage Selection by Royle's Pika (Ochotona roylei) in Jagran Forest Range, district Neelum, Azad Jammu and Kashmir, Pakistan - Ghulam Ali; Nasra Ashraf; Shahbaz Khan; Saba Khalid; Mohsin Masood (Kashmir Journal of Science)
Lagomorphs show dietary flexibility as a result of spatial and temporal distinction in the food availability which in turn influences the ecology of a species. Royle’e pika (Ochotona roylei), a specialist herbivore, is endemic to Himalayan belt. During the present study, feeding ecology of Royle’s pikas and their dietary responses to seasonal variations were examined from eighty-six study plots at Jagran Forest Range, in the northern region of Azad Jammu & Kashmir. Data of monthly diet composition, and monthly temporal changes in the selection of various food items from Royle’s pika population was collected, using focal scan sampling method, from the study plots. The overall diet of Royle’s pikas at Jagran comprised of 40.685% flowers, 15.411% mature leaves, 14.579% roots, 14.474% young leaves, 8.056% stems, 3.742% fruits, and 3.052% whole plants. The diet of pikas exhibited a wide erraticism across the study months (H = 14.989; df = 7; p = 0.0361). Royle’s pikas spent significantly more time feeding on flowers during the summer and monsoon seasons (71.23% and 78.93% respectively), than in autumn, where no flower consumption recorded. The diet of Royle’s pikas did not show a greater diversity during the study period (Shannon – Wiener index (H′) = 2.11 – 3.98); whereas, a high mean monthly dietary evenness index, was recorded (J = 0.87 – 0.99) across various study months. The results show that Royle’s pikas adapt seasonal shifts in their diet consumption as chief food items changed temporally in study area, and it is more prominent in autumn season, when ground vegetation vanishes out completely. Moreover, among various plants, Parnassia nubicola had the highest selection ratio (31.812) in the pika diet at Jagran Forest Range. The findings of the current study contribute to a better understanding of the dietary flexibility of Royle’s pikas in Western Himalayan region of Azad Kashmir, in response to local environmental conditions that may figure out lagomorph ecology and evolution.